2016
DOI: 10.1111/jonm.12387
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership in nursing and medication safety education: a discussion paper

Abstract: Aims: This paper discusses the application of transformational leadership to the teaching and learning of safe medication management. Background:The prevalence of adverse drug events (ADEs) and medication-related hospitalizations (100,000 each year in the USA) are of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 76 publications
(174 reference statements)
0
31
0
3
Order By: Relevance
“…At least, students reported that in their clinical learning setting, they perceived their impact on patient care outcomes. Also, they highlighted the need for a more combined approach to theoretical and clinical education such as, supportive learning environments with concentration on systems-based approaches to prevent errors, based on team work and systematically learning from and preventing errors [2,12]. Despite, a remarkable relapse in working in teams and management of adverse events are identified during the progress of the academic nursing program [9].…”
Section: Community Nursingmentioning
confidence: 99%
See 4 more Smart Citations
“…At least, students reported that in their clinical learning setting, they perceived their impact on patient care outcomes. Also, they highlighted the need for a more combined approach to theoretical and clinical education such as, supportive learning environments with concentration on systems-based approaches to prevent errors, based on team work and systematically learning from and preventing errors [2,12]. Despite, a remarkable relapse in working in teams and management of adverse events are identified during the progress of the academic nursing program [9].…”
Section: Community Nursingmentioning
confidence: 99%
“…Vaismoradi et al [12] argues, the nurse education, in both academic and clinical settings, can serve as a role model for socialisation and can enhance student willingness to collaborate and teach one another. Thus, in order to allow nursing students to learn how to prevent and handle adverse events it is important that they are able to work with experts from both academic and clinical setting [16].…”
Section: Community Nursingmentioning
confidence: 99%
See 3 more Smart Citations